The Use of Android-Based E-module in Teaching Pastry & Bakery Product for Vocational School Students Majoring in Culinary Arts (Journal of Vocational and Career Education, 2021)
The learning media used by teachers during online learning are not in accordance with the needs of students, so it is hard for them to understand the material and it makes learning outcomes are not optimal. Therefore, the students of class XII majoring in Culinary Arts at State Vocational High School 1 Jambu need a learning media that can be used independently and can improve the students’ learning outcomes. This study aimed to develop an android-based e-module for pastry bakery product learning, which was analyzed in terms of the feasibility, practicality, and effectiveness of the e-module.The research method used was RD with the ADDIE model. The data collection technique used was a feasibility test questionnaire by media and content experts, a practicality test questionnaire by users, and a pre-test and post-test by students. The data analysis was the mean, reproducibility coefficient (Rc) and the scalability coefficient (Sc), N-Gain difference test and t-test.The results showed that the pastry bakery e-module was feasible, practical, effective and significant in improving student learning outcomes, especially the results of croissant learning material.The conclusion of this study is the use of e-module in teaching pastry bakery product can improve students’ learning outcomes especially for croissant results. The novelty of this study is the development of an e-module on pastry bakery subjects based on an android application.